2015
DOI: 10.1007/s10853-015-9652-2
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of microstructure in AZ91 alloy processed by high-pressure torsion

Abstract: An investigation has been conducted on AZ91 magnesium alloy processed in high-pressure torsion (HPT) at 296, 423 and 473 K for different numbers of turns. The microstructure has altered significantly after processing at all processing temperatures. Extensive grain refinement has been observed in the alloy processed at 296 K with apparent grain sizes reduced down to 35 nm. Segmentation of coarse grains by twinning has been observed in the alloy processed at 423 K and 473 K with average apparent grain sizes of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…The AZ91 and the ZK60 alloys present a broader hardening stage up to strains of >20. Previous reports described strain hardening up to strains of ≈20 in ZK60 and a broad strain hardening in the AZ91 alloy . It is known that hardening is effective in preventing deformation localization and this agrees with the higher homogeneity of the hardness distribution in these alloys compared to the AZ31 alloy.…”
Section: Resultssupporting
confidence: 76%
“…The AZ91 and the ZK60 alloys present a broader hardening stage up to strains of >20. Previous reports described strain hardening up to strains of ≈20 in ZK60 and a broad strain hardening in the AZ91 alloy . It is known that hardening is effective in preventing deformation localization and this agrees with the higher homogeneity of the hardness distribution in these alloys compared to the AZ31 alloy.…”
Section: Resultssupporting
confidence: 76%
“…Figure shows the appearance of specimens of a Mg‐9% Al alloy processed by 5 turns of HPT at 423 K and pulled in tension at 473 K at different strain rates, where the elongations over 400% confirm the occurrence of superplasticity . A maximum strain‐rate sensitivity of ≈0.52 and elongations over 1000% were also reported in an AZ91 alloy …”
Section: Mechanical Propertiesmentioning
confidence: 73%
“…Later it was shown that this heterogeneity is not observed in aluminum processed using similar procedures and this demonstrates that the tendency for heterogeneity in the hardness distribution is associated specifically with magnesium. A recent report showed that a homogeneity along both the radial direction and the through‐thickness direction was achieved in an AZ91 alloy after 10 turns of HPT …”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…It has been reported that in HPT-processed AZ31 and AZ91 alloys the dislocation density, as measured by positron lifetime spectrometry and XRD, increased gradually to about ~1.2×10 14 m -2 and ~2×10 14 m -2 , respectively, after processing for the first several turns [35,36], whilst the model in [37] predicts a dislocation density of 1.4× 10 14 m -2 for pure Mg processed by HPT to a saturated hardness. In the present alloy, the dislocation density increases dramatically at the early stage, and after 10 and 16 turns, the saturated dislocation density reaches ~3.2×10 14 m -2 .…”
Section: Discussionmentioning
confidence: 99%